PELAKSANAAN TUGAS SEKSI KEAMANAN DAN KETERTIBAN RUMAH DETENSI IMIGRASI (RUDENIM) PEKANBARU - Zainal, Redho (Jurnal Ilmu Administrasi Negara, 2022)
This study aims to analyze how the Security and Order Section of the Pekanbaru Immigration Detention Center is carried out. In this study, the benchmark used is to pay attention to security, service and disposition of the security and order section. The population in this study were the Head of Rudenim, Head of Security and Order Section, Head of Security Subsection, Head of Order Subsection, Commander of Immigration Guards, and Detainees. And the entire population is used as a sample where the Head of the Rudenim is a key informant and the security and order section uses a purposive sampling technique. Then for the detainees, researchers used the Proportional Stratified Random Sampling technique to divide the population into small groups that do not overlap but represent the entire population. Data collection conducted interviews with informants, data collection with respondents was carried out by distributing questionnaires, as well as documentation and author observations to see how the implementation of the tasks of the security and order section of the Pekanbaru Immigration Detention Center analyzed using the percentage data technique to find out how many percent of respondents answered it was carried out, quite implemented and not implemented. So based on it, it can be concluded that the research on the Implementation of the Security and Order Section of the Pekanbaru Immigration Detention Center is in the "Sufficiently Implemented" category, according to the respondents' responses.